A reescrita da tragédia Alceste, de Eurípides, na novela-poema Os velhos também querem viver, de Gonçalo M. Tavares - Amâncio, Flávia (2024)
This research investigates the theme of sacrifice in the novel-poem “Os velhos também querem viver”, by Gonçalo M. Tavares, a rereading of the tragedy "Alceste", by Eurípedes, with the purpose of understanding the sacrificial act, as exclusion of oneself for a greater good, in addition to establishing connections between the works and questioning their effectiveness in practical life, since the texts, although of different genres – the first being a novel-poem and the second tragic –, are based on the same episode, but in historically different periods. The first, from 2015 and the second, from the fifth century BC. One in the modern period and the other, classical. Both are an excellent opportunity, not yet studied, to raise the reasons why we still speak and practice the sacrificial act in a secular, desacralized society